Leeuwin Current dynamics over the last 60 kyr: relation to Australian ecosystem and Southern Ocean change - Nürnberg, Dirk; Kayode, Akintunde; Meier, Karl J. F.; Karas, Cyrus (Climate of the past, 2022)
The Leeuwin Current, flowing southward along the western coast of Australia, is an important conduit for the poleward heat transport and inter-ocean water exchange between the tropical and the subantarctic ocean areas. Its past development and its relationship to Southern Ocean change and Australian ecosystem response is, however, largely unknown. Here we reconstruct sea surface and thermocline temperatures and salinities from foraminiferal-based Mg/Ca and stable oxygen isotopes from areas offshore of southwestern and southeastern Australia, reflecting the Leeuwin Current dynamics over the last 60 kyr.